Does female labor scarcity encourage innovation? Evidence from China’s gender imbalance - Tan, Zhibo; Zhang, Xiaobo (International Food Policy Research Institute, 2016)
Facing scarcity of a production factor, a firm can develop technologies to either substitute the scarce factor (price effect) or complement the more abundant factors (market size effect). Whether the market size effect or the price effect dominates largely depends on the elasticity of substitution among factors according to the theory of directed technical change. However, it is a great challenge to empirically test the theory because factor prices are often endogenously determined. In this paper, we use imbalanced sex ratios across Chinese provinces as a source of identification strategy to test how female labor scarcity affects corporate innovation based on the matched dataset of annual surveys of industrial firms in China and the national patent database. In regions with a large male population, female-intensive industries face more serious problems finding female workers than their male-intensive counterparts. We find that such female shortages have spurred firms in female-intensive industries to innovate more. The pattern is much more evident in industries with low substitution between female and male workers than in those with high substitution, consistent with the predictions of directed technical change theory.